Advancements in abiotic stress resistance in sorghum (Sorghum bicolor L.): Integrating genomics, breeding and agronomic innovation - Sushma, N; Kavithamani, D; Meena, K B; Sudha, A; Meenakshi, P (Plant Science Today, 2025)
Sorghum (Sorghum bicolor) is highly resilient to abiotic stresses such as drought, heat, salinity, cold and nutrient deficiencies, making it an important crop for food security under changing climates. This adaptability is driven by morphological and physiological traits like deep root systems, stomatal regulation, osmotic adjustment and antioxidant defense, supported by molecular mechanisms involving stress-responsive genes and transcription factors such as DREB, NAC and LEA proteins. Advances in QTL mapping, GWAS, transcriptomics, proteomics and metabolomics have revealed key pathways and candidate genes for stress tolerance, while breeding approaches including marker-assisted selection, genomic selection and the use of wild relatives have enabled the development of stress-resilient lines with stable yields. Biotechnological tools such as CRISPR/Cas9, RNA interference and overexpression further offer precise genetic improvement. Together, these strategies are accelerating the creation of climate-smart sorghum varieties for sustainable agriculture. Future research should integrate multi-omics with machine learning to decipher complex stress-response networks and strengthen interdisciplinary collaborations to breed sorghum suited for diverse agro-ecological zones.